Editorial - Melba Libia Cárdenas (Profile Issues in Teachers' Professional Development, 2012)
Welcome to this edition of the PROFILE Journal, which contains twelve articles with a variety of issues and perspectives. As we can see by its contents, all of the articles have had a steering force: The authors’ commitment to share what they know. Their knowledge derives, in turn, from what they have studied, and what they have learned as a result of teaching, research and reflective processes.